Impact of an Interprofessional Health Student Education Program on Older Adult Participants. (August 2022) - Rodgers, John; Segal-Gidan, Freddi; Reilly, Jo Marie
Training health professional students to work with older adults will improve future workforce capacity to meet growing needs. Additionally, older adults may benefit from health education and interactions with health professional students. We analyzed survey responses from older adults who had participated in an interprofessional health student education program regarding their experiences. Qualitative data were summed and averaged, and quantitative survey data were analyzed with Fisher's Exact Test. At least 60% of participants reported receiving information for health needs or making changes to physical activity, dental care, or diet. The most significant differences in lifestyle modifications were noted among racial and ethnic minorities and among speakers of different primary languages. 64% of the qualitative responses reflected positive affirmation of the program. Our data suggest that interactions with health students are meaningful experiences for older adults, are associated with healthy habit changes, and reflect demographic differences in response to health education.